Communication after laryngectomy - Hočevar-Boltežar, Irena (Radiology and oncology (Ljubljana), 2001)
Background. Laryngectomy is the mode of treatment of the patients with advanced laryngeal and hypopharyngeal cancer. It affects many important functions, including speech. Patients and methods. Various alaryngeal speech modes are available so that no laryngectomee should be left without a means ofcommunication. Results. There is a variety of artificial devices, including electronic ones that produce their own battery driven sound. Alternatively, the patient can learn a new form of voicing using a muscular segment of the upper esophagus as a source of sound (esophageal speech). A puncture can be created surgically through the esophageal wall and a prosthesis placed in it to divert pulmonary air into the esophagus and through the same muscular segment to produce sound. Conclusions. Many factors influence the choice of analternative to be used with a particular patient. In Slovenia, esophageal speech is the most frequently used alaryngeal speech mode.
Keywords: govor; Govor alaringealni; grlo; Grlo umetno; Grlo, novotvorbe; komunikacija; Laringektomija; Laryngeal neoplasms; Laryngectomy; Larynx, artificial; rak (medicina); Speech, alaryngeal; Speech, esophageal